Universıty Employees’ Healthy Lifestyle Behaviors And Fastıng Blood Glucose - Ertürk, Nuriye Efe; Aslan, Sinan; Ercan, Selami; Çeçen, Sultan; Çınar, Ercan; Demir, Zeynel Abidin; İnci, Ramazan (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Adopting healthy lifestyle behaviors is an important step in preventing diseases. Objective: This study aims to determine healthy lifestyle behaviors, fasting blood glucose (FBG) levels, and waist circumference of employees in a public university in Turkiye. Methods: This descriptive study was conducted. A total of 191 academic and administrative staff were recruited for this study.We used sociodemographic data form and the Health-Promoting Lifestyle Profile II (HPLP II) for data collection. We measured and recorded each participant’s FBG (at least 8 hours), height, weight, and waist circumference in the data sheet. Results: Of the participants, 77% were aged under 40; 74.9% were male; 71.2% were administrative staff; 48.2% had FBG between 100-125 mg/dl.; 49.2% were within the normal BMI (Body Mass Index) range; 29.2% of women had a waist circumference greater than 90 cm, 25.2% of men had a waist circumference greater than 100 cm. The average HPLP II score of the participants was 128.67±18.51. Conclusion: It was determined that healthy lifestyle behaviors did not change according to age, that 48.2% of the participants had FBG between 100-125 mg/dl and were not aware of their blood glucose levels, that half of the participants were overweight and obese, and that waist circumference and FBG increased as BMI increased. The incidence of diabetes might be higher than predicted in guidelines in near future. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 383-392